Utilization of Pineapple Waste: A Review - Upadhyay, Atul; Lama, Jeewan Prava; Tawata, Shinkichi (Journal of Food Science and Technology Nepal, 2013)
Waste utilization in fruits and vegetable processing industries is one of the important and challengeable jobs around the world. It is anticipated that the discarded fruits as well as its waste materials could be utilized for further industrial purposes viz. fermentation, extraction of bioactive components, extraction of functional ingredients etc. Researchers have focused on the utilization of pineapple waste primarily for extraction of bromelain enzyme and secondarily as low-cost raw material for the production of ethanol, phenolic anti-oxidants, organic acids, biogas and fiber production. Pertinent scientific and technological implications would produce better and more profitable markets for pineapple wastes. This review is the collection of previous reports along with our ongoing work on utilization of pineapple wastes J. Food Sci. Technol. Nepal, Vol. 6 (10-18), 2010 DOI: http://dx.doi.org/10.3126/jfstn.v6i0.8255